The relationship between acceptance of mobile technology and perceived work performance improvement among employees at Mycron Steel Crc Sdn Bhd / Mimie Shahila Asmat - Asmat, Mimie Shahila (2019)
This research investigated the relationship between acceptance of mobile technologies and perceived work performance improvement at Mycron Steel Sdn. Bhd. Shah Alam, Selangor. The research was applied UTAUT model that consists of four independent variables namely performance expectancy, effort expectancy, facilitating conditions, and social influence and one dependent variable which is perceived work performance improvement. The sampling technique that was used is stratified random sampling. The researcher used questionnaires as the instrument for primary data collection. The objective of this research is to study the relationship between acceptance of mobile technology and perceived work performance improvement among employees at Mycron Steel Crc Sdn Bhd. The second objective is to identify the most important variable of mobile technology acceptance toward perceived work performance improvement. The methodology used in this study discussed and explain through research design, sampling frame, population, sample technique, sample size, unit of analysis, instrument, data collection procedures, and data analysis. A total respondent in Mycron Steel Crc Sdn Bhd from all department is 132 respondents. The statistic of data analysis is using a Pearson Coefficient Correlation to identify the relationship between acceptance of mobile technology and perceived work performance improvement and the descriptive analysis was used to measure the mean values. The finding from the study shows that, the respondents agree that there are significant relationships between Performance Expectancy, Effort Expectancy, Facilitating Conditions, Social Influences and Perceived Work Performance Improvement